A study on the symptoms, sleep quality and cognitive function of the women during menopause - S. H., Fiza; N., Manaswi; Preman, Pavithra; Hari, Gopika; Kalyan, Pavan; Sajan, Tesmi (International Journal of Research in Medical Sciences, 2024)
Background: Menopause is the time that marks the end of your menstrual cycle. It is a natural biological process. But the physical symptoms, such as hot flashes, and emotional symptoms of menopause may disrupt your sleep, lower your energy or affect emotional health. The primary objective of the study was to evaluate the pattern of symptoms among women during menopause. The secondary objective was to assess the sleep quality and cognitive function of the women during menopause and to create awareness and educate rural women regarding menopause. Methods: A cross-sectional observational study was carried out in and around B. G. Nagar, Nagamangala, Mandya for 6 months. Results: A total of 504 women were enrolled in the study. Out of 504, 224 (44.4%) participants come under perimenopause, 117 (23.31%) participants come under perimenopause and 163 (33.34%) participants comes under post menopause. After filling out the questionnaire it was observed that there was a decline in cognitive function of postmenopausal women along with poor sleep quality. When the age group of the participants was compared with the different symptoms of menopause a significant relation was found between the age category of the participants and the somatic symptoms. A significant relation was found between the sexual activity and with the somatic symptoms (p=0.00**), psychological symptoms (p=0.00**) and urogenital symptoms (p=0.00**) of the participants. Conclusions: As women passes from premenopausal to perimenopause to post menopause menopausal symptoms were increased. The menopausal transition and postmenopausal years are associated with significant symptoms.